Polio vaccination coverage and seroprevalence of poliovirus antibodies after the introduction of inactivated poliovirus vaccines for routine immunization in Japan - Satoh, Hiroshi; Tanaka-Taya, Keiko; Shimizu, Hiroyuki; Goto, Akiko; Tanaka, Shizuka; Nakano, Tsuyoshi; Hotta, Chiemi; Okazaki, Terue; Itamochi, Masae; Ito, Miyabi; Okamoto-Nakagawa, Reiko; Yamashita, Yasutaka; et al. (Vaccine, 2019)
•Sabin-derived IPV was introduced to routine immunization in Japan in 2012.•Seroprevalence of poliovirus antibody was examined after IPV introduction in Japan.•Polio vaccination coverage in children remained high even after IPV introduction.•Seropositivity rates for poliovirus in children increased after IPV introduction.•Seropositivity rates for all 3 types were high in children receiving IPV. In Japan, the oral poliovirus vaccine (OPV) was changed to 2 types of inactivated poliovirus vaccine (IPV), the standalone conventional IPV (cIPV) and the Sabin-derived IPV combined with diphtheria-tetanus-acellular pertussis vaccine (DTaP-sIPV), for routine immunization in 2012. We evaluated polio vaccination coverage and the seroprevalence of poliovirus antibodies using data from the National Epidemiological Surveillance of Vaccine-Preventable Diseases (NESVPD) from 2011 to 2015. Several years before the introduction of IPV in 2012, OPV administration for children was refused by some parents because of concerns about the risk of vaccine-associated paralytic poliomyelitis. Consequently, in children aged <1 years who were surveyed in 2011–2012, polio vaccination coverage (45.0–48.8%) and seropositivity rates for poliovirus (type 1: 51.7–65.9%, type 2: 48.3–53.7%, and type 3: 15.0–29.3%) were decreased compared to those surveyed in 2009. However, after IPV introduction, the vaccination coverage (95.5–100%) and seropositivity rates (type 1: 93.2–96.6%, type 2: 93.1–100%, and type 3: 88.6–93.9%) increased among children aged <1 years in 2013–2015. In particular, seropositivity rates and geometric mean titers (GMTs) for poliovirus type 3 in <5-year-old children who received 4 doses of IPV (98.5% and 247.4, respectively) were significantly higher than in those who received 2 doses of OPV (72.5% and 22.9, respectively). Furthermore, in <5-year-old children who received 4 doses of either DTaP-sIPV or cIPV, the seropositivity rates and the GMTs for all 3 types of poliovirus were similarly high (96.5–100% and 170.3–368.8, respectively). Our findings from the NESVPD demonstrate that both the vaccination coverage and seropositivity rates for polio remained high in children after IPV introduction.